2007
DOI: 10.1128/jcm.00228-07
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Melioidosis in the Er-Ren River Basin, Taiwan: Implications for Transmission

Abstract: . The objective of this study was to determine the association between the level of exposure to Burkholderia pseudomallei and the incidence rate of melioidosis and to survey the transmission modes of B. pseudomallei in the Er-Ren River Basin. The serosurveillance of melioidosis gave seropositivity rates of 36.6%, 21.6%, and 10.9%, respectively, for residents in regions A, B, and C within the Er-Ren Basin area. Culture and PCR-based detection of B. pseudomallei from soil demonstrated that the geographical distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
52
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 25 publications
0
52
0
Order By: Relevance
“…However, the number of melioidosis cases suddenly increased in the Er-Ren River Basin in southern Taiwan after a typhoon followed by a flood in 2005 (8,9). B. pseudomallei was isolated from agricultural crop soil, and the prevalence of B. pseudomallei-specific antibodies increased significantly among residents after the typhoon and flood incident (9). This raises the question of the extent to which B. pseudomallei is found in soil (natural environments) in Taiwan.…”
mentioning
confidence: 96%
See 3 more Smart Citations
“…However, the number of melioidosis cases suddenly increased in the Er-Ren River Basin in southern Taiwan after a typhoon followed by a flood in 2005 (8,9). B. pseudomallei was isolated from agricultural crop soil, and the prevalence of B. pseudomallei-specific antibodies increased significantly among residents after the typhoon and flood incident (9). This raises the question of the extent to which B. pseudomallei is found in soil (natural environments) in Taiwan.…”
mentioning
confidence: 96%
“…These cases were categorized as being acquired during prior travels to areas of endemicity overseas rather than by indigenous acquisition, because the confirmed cases were rare and the pathogens were never isolated from the environment. However, the number of melioidosis cases suddenly increased in the Er-Ren River Basin in southern Taiwan after a typhoon followed by a flood in 2005 (8,9). B. pseudomallei was isolated from agricultural crop soil, and the prevalence of B. pseudomallei-specific antibodies increased significantly among residents after the typhoon and flood incident (9).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Chen et al recommends the fliC method with the possible addition of another PCR method (Dharakul et al, 1999) for detection of B. pseudomallei in soil samples. In fact, two epidemiological studies used Wajanarogana et al's and Dharakul et al's assays and reported that PCR was usually inferior to serology, but superior to culture in detecting B. pseudomallei in soil samples (Su et al, 2007;Chen et al, 2010). Chen et al's epidemiological study revealed 53 soil samples that were confirmed positive by Wajanarogana et al's and Dharakul et al's tests, but were negative by culture, indicating PCR sensitivity beyond culture (Chen et al, 2010 .…”
Section: Pcr Methods To Detect and Differentiate The Burkholderia Psementioning
confidence: 96%